Zebrafish Models in Therapeutic Research of Cardiac Conduction Disease - Gao, Rui; Ren, Jie (Frontiers in Cell and Developmental Biology, 2021)
Malfunction in the cardiac conduction system (CCS) due to congenital anomalies or diseases can cause cardiac conduction disease (CCD), which results in disturbances in cardiac rhythm, leading to syncope and even sudden cardiac death. Insights into development of the CCS components, including pacemaker cardiomyocytes (CMs), atrioventricular node (AVN) and the ventricular conduction system (VCS), can shed light on the pathological and molecular mechanisms underlying CCD, provide approaches for generating human pluripotent stem cell (hPSC)-derived CCS cells, and thus improve therapeutic treatment for such a potentially life-threatening disorder of the heart. However, the cellular and molecular mechanisms controlling CCS development remain elusive. The zebrafish has become a valuable vertebrate model to investigate early development of CCS components because of its unique features such as external fertilization, embryonic optical transparency and the ability to survive even with severe cardiovascular defects during development. In this review, we highlight how the zebrafish has been utilized to dissect the cellular and molecular mechanisms of CCS development, and how the evolutionarily conserved developmental mechanisms discovered in zebrafish could be applied to directing the creation of hPSC-derived CCS cells, therefore providing potential therapeutic strategies that may contribute to better treatment for CCD patients.